2000
DOI: 10.1063/1.1330754
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure process to produce GaN crystals

Abstract: High melt temperature and thermal decomposition prevent the use of standard bulk semiconductor crystal growth processes for the production of GaN. We have employed a hydrostatic pressure system to grow GaN crystals. An ultrahigh pressure, high temperature process was developed using a solid-phase nitrogen source to form GaN crystals in a Ga metal melt. Using a thermal gradient diffusion process, in which nitrogen dissolves in the high temperature region of the metal melt and diffuses to the lower temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The weak component on the higher frequency side at ∼577 cm −1 is due to sapphire, while the two component peaks on the lower frequency side at ∼558 cm −1 and ∼532 cm −1 are close to the reported values for E 1 (TO) and A 1 (TO) phonon modes, respectively [44,45]. The presence of these component peaks is indicative of the deviations from back scattering geometry [46], and the increase of their prominence in the films grown at lower N 2 percentages may be attributed to misalignment of crystallites and possible increase in disorder [47]. The variation of E 2 (high) peak position (obtained after deconvolution) with Ar and N 2 percentages is shown in figure 4(b), along with the standard value of the mode.…”
Section: Resultssupporting
confidence: 79%
“…The weak component on the higher frequency side at ∼577 cm −1 is due to sapphire, while the two component peaks on the lower frequency side at ∼558 cm −1 and ∼532 cm −1 are close to the reported values for E 1 (TO) and A 1 (TO) phonon modes, respectively [44,45]. The presence of these component peaks is indicative of the deviations from back scattering geometry [46], and the increase of their prominence in the films grown at lower N 2 percentages may be attributed to misalignment of crystallites and possible increase in disorder [47]. The variation of E 2 (high) peak position (obtained after deconvolution) with Ar and N 2 percentages is shown in figure 4(b), along with the standard value of the mode.…”
Section: Resultssupporting
confidence: 79%
“…In this context worth indicating is the recent discussion on GaN thermochemical and related kinetics of crystals formation and decomposition at HP-HT conditions [6,25]. Notable are also innovative HP-HT solutions in which the process is developed using a solid-phase nitrogen source to form GaN crystals in a Ga metal melt [6,26].…”
Section: Introductionmentioning
confidence: 99%
“…9 Davydov et al assessed the thermochemical and pressuretemperature-composition phase diagram data for the Ga-N system. 4 Although a few reports have suggested that the melting point is greater than 2500 K, there has been no systematic study on this issue. On the other hand, an attempt to perform a high-mechanical-pressure and high-temperature process was made in order to synthesize high-quality GaN crystals in the system containing no free volume for an ambient gas.…”
Section: Introductionmentioning
confidence: 99%